The validity and reliability of commercially available resistance training monitoring devices: A systematic review - Weakley, J.; Morrison, M.; García-Ramos, A.; Johnston, R.; James, L.; Cole, M. H. (Sports Medicine, 2021)
Background: Monitoring resistance training has a range of unique difficulties due to differences in physical characteristics and capacity between athletes, and the indoor environment in which it often occurs. Traditionally, methods such as volume load have been used, but these have inherent flaws. In recent times, numerous portable and affordable devices have been made available that purport to accurately and reliably measure kinetic and kinematic outputs, potentially offering practitioners a means of measuring resistance training loads with confidence. However, a thorough and systematic review of the literature describing the reliability and validity of these devices has yet to be undertaken, which may lead to uncertainty from practitioners on the utility of these devices.